STUDI TENTANG PERILAKU ORGANISASI PADA SEKOLAH MENENGAH ATAS NEGERI PROVINSI DKI JAKARTA - Jimmy Herman, - (2006)
A Study on Organizational. Behavior jn State Senior High School in the Province of DKÏ Jakarta. (Analysis of die relationship between organizational commitment, personality traits, teacher's competency, micro culture, and locus of control with the teacher's performance. Disertation. Bandung: Postgraduate Program. Indonesia University of Education.This research was conducted in the Excellent State Senior High School in the Province of DKI Jakarta. This study was aimed as finding out the relationship between organizational commitment, personality traits, teacher's competency, micro culture, and locus of control with the teacher's performance. The method used was survey with quantitative approach. Using valid and reliable instruments. The data of the respondents' perception were analyzed statistically. The population of this research is 670 teachers. The sample is 80 teachers recruited by using multistage random sampling techniques. The organizational commitment, personality traits and teacher's competency were analyzed as independent variables; the micro culture and locus of control were analyzed as moderating variables; whereas teacher's performance as dependent variable.Affected by moderating variables, there are positive relationship between independent variables with dependent variable. Positive relationship between organizational commitment with teacher's performance indicated by correlation coefficient 0,5808. Positive relationship between personality traits with teacher's performance indicated by correlation coefficient 0,7239. Positive relationship between teacher's competence with teacher's performance indicated by correlation coefficient 0,7594. Positive relationship between those independent variables, affected by moderating variables with teacher's performance, represented by correlation coefficient 0,8703,As a result of scientific research^ can be socialized to other schools in Indonesia, as a basic policy to improve the teacher's performance. Improving the teacher's performance seem to be important to all schools, bccause teachers are key implemcnter of the principal's policy, which vertically and strategically follow the national educational policy of the government.With effective socialization and coordination among the schools, the researcher hope this research will create networking as partnership strategies, improve the degree of collaboration, which high school is a subsystem of the national educational system.